The Effect of Systemic Doxycycline and Mechanical Therapy on GCF β-Glucuronidase Leves in Chronic Periodontitis Patients - Zia, Afaf; Gupta, Narendra; Bey, Afshan; Khan, Asad U; Khan, Saif; Andarabi, Syed Mukhtar Un Nisar; Khan, Rosina; Adil, Mohd (UI Scholars Hub, 2017)
The goal of periodontal therapy includes management of bacterial pathogens to control the destruction of the periodontal tissue. A number of different nonsurgical and surgical therapies have been used in achieving this goal. Objective: To evaluate the effectiveness of doxycycline compared with nonsurgical therapy alone or in combination with nonsurgical therapy on gingival crevicular fluid β-Glucuronidase levels (ßG) and clinical parameters over a 20-week period in patients with chronic periodontitis. Methods: An interventional study comprising 60 patients with chronic periodontitis. They were divided into three groups of different treatment approach. The plaque index, gingival index, probing depth, and clinical attachment levels were recorded, and gingival crevicular fluid (GCF) samples were collected at 2, 6, 10, and 20 weeks, after treatment. Results: The levels of GCF βG and clinical parameters were higher when the treatment was initiated, and the levels decreased after treatment. No significant difference was found in the βG level when nonsurgical therapy and doxycycline were used alone. In comparison, when doxycyline and nonsurgical therapy were combined, the level of βG decreased significantly. Conclusion: The present study indicated the usefulness of doxycycline as an adjunct to nonsurgical periodontal therapy in lowering GFC βG levels and clinical parameters.